Distribution and Source Apportionment of Polycyclic Aromatic Hydrocarbons in Soils at Different Distances and Depths around Three Power Plants in Bijie, Guizhou Province. (16th March 2023) - Liu, Jialin; Zhang, Shuyue; Jia, Jianli; Lou, Manjun; Li, Xiao; Zhao, Shenwei; Chen, Wei; Xiao, Bing; Yu, Yan
Abstract: In this study, 16 polycyclic aromatic hydrocarbons (PAHs) optimally controlled by the U.S. Environmental Protection Agency (EPA) were investigated. Three representative coal-fired power plants were selected as the research areas in Bijie, Guizhou Province, and 24 soil samples were collected totally from power plants at different depths and at different distances from the point pollution sources (plants). The physicochemical properties and microbial characteristics of the soil from the three power plants were also studied. The results showed that 16 PAHs were detected in all soils of the three power plants, with total concentrations ranging from 0.2 to 12.2 mg kg −1, and that PAHs in the soils were mainly 2, 3 rings with percentages ranging from 42% to 82%. The proportions of low molecular weight (LMW) PAHs were higher near the contaminated plants. Moreover, since they were easily dispersed further away with atmospheric transfer, the proportions of lighter LMW PAHs were also higher far from the point source, while the proportions of heavier high molecular weight (HMW) PAHs were higher at some distance from the point source. In addition, the distribution patterns of PAHs in the soil at different depths were slightly different because the microbial activity in the surface soil at each sampling site was greater than that in the deeper soil, and the leaching behavior of each compound was different. Finally, based on the principal component analysis (PCA) method, coal combustion is not the only source of PAHs in soils from power plants, and vehicle emissions cannot be negligible.